2013
DOI: 10.1111/aos.12237
|View full text |Cite
|
Sign up to set email alerts
|

Systemic application of sphingosine 1‐phosphate receptor 1 immunomodulator inhibits corneal allograft rejection in mice

Abstract: . Purpose:  This study aims to investigate the effects of systemic application of sphingosine 1‐phosphate receptor 1(S1P1) on allogeneic corneal transplantation in mice. Methods:  A total of 112 BALB/c mice received corneal grafts from C57BL/6 donors. Recipients were randomly divided into seven groups and treated with intraperitoneal injections of S1P1 (5 mg/kg/days), cyclosporine A (5 mg/kg/days), dexamethasone (1 mg/kg/days) and rapamycin (2 mg/kg/days). S1P1was combined with rapamycin or cyclosporine A, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In skin cancer, unbalanced mTOR signalling leads to UV-induced hyperproliferation and malignant transformation, thus indicating that mTOR may be involved in pterygium pathology 6 . Other studies have found that rapamycin inhibits corneal neovascularisation 7 , transplant rejection 8 and the epithelial-to-mesenchymal transition (EMT) of the lens epithelium 9 . Moreover, rapamycin has also been reported to promote the apoptosis of human lens epithelial cells (LECs) and to inhibit the proliferation of rabbit LECs 10 – 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In skin cancer, unbalanced mTOR signalling leads to UV-induced hyperproliferation and malignant transformation, thus indicating that mTOR may be involved in pterygium pathology 6 . Other studies have found that rapamycin inhibits corneal neovascularisation 7 , transplant rejection 8 and the epithelial-to-mesenchymal transition (EMT) of the lens epithelium 9 . Moreover, rapamycin has also been reported to promote the apoptosis of human lens epithelial cells (LECs) and to inhibit the proliferation of rabbit LECs 10 – 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Along these lines, ocular administration of rapamycin has improved the engraftment of corneal allografts. 30,31 Rapalog administration directly to the eye (either intravitreally or subretinally, the latter requiring specialized equipment) could be advantageous in bypassing the potential for systemic toxicity associated with rapalogs. Pharmaceuticals that eliminate the retinal toxicity of VGB would provide a major advance in epilepsy treatment, and our studies suggest that mTOR inhibitors should receive further preclinical attention as a therapeutic modality to potentially mitigate VGB-induced visual field pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Serum gamma interferon (IFN-␥) levels were determined using an ELISA kit (MultiSciences Biotech Co., Ltd., Hangzhou, China) (17), and serum interleukin 5 (IL-5) levels were measured using an ELISA kit (eBioscience Inc., San Diego, CA, USA). Serum cytokine levels were evaluated by interpolation of cytokine standard curves.…”
Section: Methodsmentioning
confidence: 99%